Lean Supply Chain Strategy In Agribusiness Products: Systematic Literature Review - Lumban Toruan, Juli Winando; Sarah Febrianti Sirait; Yanti Nuraeni Muflikh (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The trend change in using e-commerce from retail to culinary has an impact on the increasing number of UMKM partnering with food delivery e-commerce. The problem is only 36 percent of the 30 million UMKM targeted by the government to go online in 2024. The purpose of this study is to determine the role of food delivery e-commerce in increasing UMKM revenue. One of the UMKM has partnered with food delivery e-commerce is Nayo Salad. The research population is Nayo Salad consumers who shop using food delivery e-commerce grabfood, gofood and shopeefood. The sample of this study were 120 people. The study was conducted with a quantitative approach, to see the relationship between purchasing decisions with reasons to buy, food delivery e-commerce used and payment methods used by consumers. The results show that there are differences in the number of UMKM revenues before and after partnering with food delivery e-commerce. The results of this research hoped can be a motivation, example and raw model for other UMKM that have not partnered with food delivery e-commerce.Keywords: Revenue, Before, After, E-commerce, E-wallet, CODl